An extended PFAS profiling of a Swedish subpopulation and mixture risk assessments using multiple approaches - Josefin A. Engelhardt; Merle M. Plassmann; Jana M. Weiss (Environment International)
Per- and polyfluoroalkyl substances (PFAS) have been detected worldwide, from the deep seas to polar regions. A previous review showed that PFAS are risk drivers of the chemical mixture present in human blood. This study focused on establishing the PFAS exposure of a Swedish subpopulation and investigated whether the exposure poses a risk of adverse health effects. Human serum from 60 blood donors in Stockholm, Sweden, was analyzed. A target method including 32 PFAS analytes and over 270 suspect features was used to detect and quantify PFAS. Twenty-six PFAS were quantified, and 7 suspect PFAS features (6 H-PFCAs and PFECHS) were semi-quantified. Nine mixture risk assessment (MRA) strategies were used to assess the risk of health outcomes. Fifteen effect levels were derived and used, along with 15 already established values. The certainty of various derivation techniques was discussed. The MRAs showed that the entire studied population exceeded some of the risk thresholds, with effects including high cholesterol and immune suppression. However, the certainty was lower when deriving these two effect levels. The MRA, using human biomonitoring guidance values (high certainty), concluded that for 63 % of the individuals, a risk for adverse health effects cannot be excluded. This study has demonstrated that there is a reason for concern regarding PFAS exposure in the general population of Sweden. To our knowledge, this is the first time the H-PFCAs have been semi-quantified in human blood using a reference standard.